VALIDATING THE MULTIDIMENSIONAL SCALE OF PERCEIVED SOCIAL SUPPORT FOR THE SOUTH KOREAN ADULTS IN TIMES OF THE COVID-19 PANDEMIC - Han, Shin-Il (International Online Journal of Education and Teaching, 2024)
This study arose from interest in whether the Multidimensional Scale of Perceived Social Support (MSPSS) would still be valid as a measure of social support under the conditions of the COVID-19 lockdown restrictions. A validation study of the MSPSS was undertaken in Korea in 2021 during the worst of the COVID-19 pandemic using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). Specifically, a sample of 1,434 adults completed a self-administrated survey, and among them, 741 were randomly selected for the EFA and the remainder were used for the CFA. Among the study results, ⓐ suitability tests of the sample data for factor analysis were performed, and the Kaiser–Meyer–Olkin statistic was sound for sampling adequacy; additionally, skewness and kurtosis indicated normal distributions of all the items, and the homogeneity of the scale was supported by the strong positive correlations between each item and the total. Additionally, ⓑ EFA revealed satisfactory internal consistency and homogeneity, with significant positive correlations among the three factors (significant others, family, and friends); testing showed that the three-factor structure of the original 12-item MSPSS was still appropriate. The concurrent validity of the MSPSS was measured by examining its correlations with similar constructs such as stress, loneliness, and depression, and all correlations were statistically negatively significant, implying that perceptions of social support are associated with better mental or emotional health. ⓒ CFA was also conducted to validate the original MSPSS three-factor model structure in a different sample of subjects, and these results also validated the three-factor model based on sound fit indices. Implications of the results are suggested.